If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4(16 + -1x) = 40 2x + (16 * 4 + -1x * 4) = 40 2x + (64 + -4x) = 40 Reorder the terms: 64 + 2x + -4x = 40 Combine like terms: 2x + -4x = -2x 64 + -2x = 40 Solving 64 + -2x = 40 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-64' to each side of the equation. 64 + -64 + -2x = 40 + -64 Combine like terms: 64 + -64 = 0 0 + -2x = 40 + -64 -2x = 40 + -64 Combine like terms: 40 + -64 = -24 -2x = -24 Divide each side by '-2'. x = 12 Simplifying x = 12
| 0.075(x+2000)=0.08x+0.06(2000) | | X^2-36= | | .3x+.12=3.72 | | 3x-6y-2=16 | | 3t^2-48t+180=0 | | 9-26x=36 | | y-6=-25 | | 1/7(3y+2)=2+1/3(y+2) | | 3x-6y+2=16 | | 3y-6x+2=16 | | 5(x-3)=-40 | | -26-15x=19 | | 5x^2+2x-9=0 | | 2x=3x+5+865 | | -15x-26=19 | | (7z-3)(z+5)-(7z-3)(z-4)= | | 5t-2t=16 | | x*5+250=x*15-10 | | 4=18+x | | 14x+18=-10 | | 0.5(x^2+8x)= | | 4(x-5)=4x-5 | | 5x+4=3[2x-1] | | -5x-6=16 | | 4(x-5)=4x | | -8y=-6 | | 6p=-9 | | 13-9x=42-16x | | 3a-(5a+7)=20 | | -9y=-2 | | (2x+8)+(x+8)=52 | | n+(n+1)+(n+2)+(n+3)+(n+4)+(n+5)+(n+6)+(n+7)+(n+8)+(n+9)+(n+10)=x^3 |